2020
DOI: 10.7554/elife.50532
|View full text |Cite
|
Sign up to set email alerts
|

Sperm chemotaxis is driven by the slope of the chemoattractant concentration field

Abstract: Spermatozoa of marine invertebrates are attracted to their conspecific female gamete by diffusive molecules, called chemoattractants, released from the egg investments in a process known as chemotaxis. The information from the egg chemoattractant concentration field is decoded into intracellular Ca2+ concentration ([Ca2+]i) changes that regulate the internal motors that shape the flagellum as it beats. By studying sea urchin species-specific differences in sperm chemoattractant-receptor characteristics we show… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Conspecific chemoattractant preference has been demonstrated in the abalone species H. rufescens and H. fulgens (Riffell et al, 2004 ), although the interaction of gamete recognition proteins is a better predictor of fertilization success in these species (Evans & Sherman, 2013 ). Sperm chemotaxis has also been described in the sea urchins Arbacia puctulata (Ward et al, 1985 ), Lytechinus pictus (Guerrero et al, 2010 ), and S. purpuratus (Ramírez‐Gómez et al, 2020 ).…”
Section: Discussionmentioning
confidence: 96%
“…Conspecific chemoattractant preference has been demonstrated in the abalone species H. rufescens and H. fulgens (Riffell et al, 2004 ), although the interaction of gamete recognition proteins is a better predictor of fertilization success in these species (Evans & Sherman, 2013 ). Sperm chemotaxis has also been described in the sea urchins Arbacia puctulata (Ward et al, 1985 ), Lytechinus pictus (Guerrero et al, 2010 ), and S. purpuratus (Ramírez‐Gómez et al, 2020 ).…”
Section: Discussionmentioning
confidence: 96%
“…The results showed that simulations without desensitization lost the chemotactic function (Figures 2A,B and 3A,B), suggesting that sperm desensitization through GC dephosphorylation is essential for long-range chemotaxis in sea urchins and starfish. In other species ascidian sperm exhibit different signal transduction, in which the sperm responds to the dissociation of the chemoattractant from its receptor [33], whereas in other sea urchins, Lytechinus pictus and Strongylocentrotus purpuratus, the gradient of chemoattractant evokes [Ca 2+ ] i oscillation in the sperm, producing a response involving a series of turns toward the egg [34]. It is possible that desensitization system functions in long-range chemotaxis of these animals, even though the signaling pathways are not similar.…”
Section: Discussionmentioning
confidence: 99%
“…Resact is a small 14 amino acid polypeptide that attracts the migration of sperm in Arbacia punctualata (Ramirez-Gomez et al, 2020;Ward et al, 1985). Pretreatment of sperm with resact inhibits their ability to have a chemotatic response, indicating that sperm chemotaxis can be a significant step in fertilization and important for reproductive fitness (Ward et al, 1985).…”
Section: Sperm Chemotaxismentioning
confidence: 99%
“…Pretreatment of sperm with resact inhibits their ability to have a chemotatic response, indicating that sperm chemotaxis can be a significant step in fertilization and important for reproductive fitness (Ward et al, 1985). Sea urchin speract is a decapeptide released by the egg and is known to increase sperm motility and cause chemotaxis to the egg in the species Stronglycentrotus purpuratus and Lytechinus pictus (Hussain et al, 2016;Ramirez-Gomez et al, 2020).…”
Section: Sperm Chemotaxismentioning
confidence: 99%